Investigation of the relationship between the evaporation and meteorological variables for different Class A pan treatments - Simon-Gáspár, Brigitta; Soós, Gábor; Anda, Angéla (GEORGIKON FOR AGRICULTURE, 2022)
Evaporation is a key member of the hydrological cycle. Climate change requires a more accurate understanding of the process. In addition to physical processes, the evaporation of open water is also influenced by biological factors (eg aquatic plants). To better understand the phenomenon, an experiment has been set up in 2020 growing season: in addition to the traditional use of Class A pan (WMO), the presence of sediment and submerged macrophyte (Myriophyllum sp., Potamogeton sp., and Najas sp.) was also ensured in the Class A pan's. The Class A pan's were located in an open area at the Agrometeorological Research Station in Keszthely. Meteorological variables were also measured at the Station (air temperature, precipitation, relative humidity, solar radiation, wind speed). The aim of the study was to determine the effect of sediment and macrophyte on evaporation and explore the relationship between evaporation and meteorological variables. The results showed that the presence of both sediment and submerged macrophyte increased evaporation. Among the meteorological variables, solar radiation and air temperature showed the closest relationship with evaporation.
Keywords: evaporation; class A pan; sediment; macrophytes